Pengaruh Aspek-Aspek Kemakmuran Negara terhadap Kepatuhan Pajak - Margareta Dewi Perbawaningsih; Ari Budi Kristanto (Jurnal Penelitian Teori & Terapan Akuntansi (PETA), 2021)
This study aims to examine the influence of country prosperity aspects towards tax compliance. The aspets consist of inclusive society, empowered people, and open economy. This study uses secondary data including the country prosperity index report from The Legatum Institute Foundation and the Level of Tax Effort. The population in this study are countries around the world and based on purposive sampling, 94 countries were sampled. This research hypothesis testing uses multiple regression analysis, and previously the data had been tested using the classical assumption test. The results of this study indicate that inclusive society and empowered people have a positive effect on tax compliance, while the open economy variable has a negative effect on tax compliance. The results of this study are expected to be a consideration by the government in making tax policies as an effort to achieve the tax compliance, particularly in encouraging inclusive and empowered society.